Autonomic control of post-air-breathing tachycardia in Clarias gariepinus (Teleostei: Clariidae) - Teixeira, Mariana Teodoro [UNESP]; Armelin, Vinicius Araújo; Abe, Augusto Shinya [UNESP]; Rantin, Francisco Tadeu; Florindo, Luiz Henrique [UNESP] (Springer Nature, 2015)
The African catfish (Clarias gariepinus) is a teleost with bimodal respiration that utilizes a paired suprabranchial chamber located in the gill cavity as an air-breathing organ. Like all air-breathing fishes studied to date, the African catfish exhibits pronounced changes in heart rate (f H) that are associated with air-breathing events. We acquired f H, gill-breathing frequency (f G) and air-breathing frequency (f AB) in situations that require or do not require air breathing (during normoxia and hypoxia), and we assessed the autonomic control of post-air-breathing tachycardia using an infusion of the β-adrenergic antagonist propranolol and the muscarinic cholinergic antagonist atropine. During normoxia, C. gariepinus presented low f AB (1.85 ± 0.73 AB h−1) and a constant f G (43.16 ± 1.74 breaths min−1). During non-critical hypoxia (PO2 = 60 mmHg), f AB in the African catfish increased to 5.42 ± 1.19 AB h−1 and f G decreased to 39.12 ± 1.58 breaths min−1. During critical hypoxia (PO2 = 20 mmHg), f AB increased to 7.4 ± 1.39 AB h−1 and f G decreased to 34.97 ± 1.78 breaths min−1. These results were expected for a facultative air breather. Each air breath (AB) was followed by a brief but significant tachycardia, which in the critical hypoxia trials, reached a maximum of 143 % of the pre-AB f H values of untreated animals. Pharmacological blockade allowed the calculation of cardiac autonomic tones, which showed that post-AB tachycardia is predominantly regulated by the parasympathetic subdivision of the autonomic nervous system.
Keywords: African Catfish; Autonomic control; Air Breathing; Hypoxia; Tachycardia